Activities Ukrainian diaspora USA and Canada in XX century – early XXI century after materials of fund collection national museum of Ukraine history - Mariya Sribna (Американська історія і політика, 2017)
The material of Ukrainian diaspora life and activity in the USA and Canada in the National Museum of Ukrainian History collection is analyzed in the article. History of completing of materials and transferring of interesting exhibits during years of the Ukrainian independence is traced. Based on the wide circle of historical sources, the author confirms that the National Museum of Ukrainian History has the biggest collection from the ancient time until the nowadays, which consist of about one thousand exhibits. Scientists of the museum always try to fill the museum’s funds and collections. It is noted that methodology of the accumulation of material is based on primarily completing material of the most actual themes. The importance of the theme of data research is caused by need of investigation of Ukrainian diaspora role in the process of democratization and transformation of Ukraine, transferring of positive experience in the development of civil society, underlining of diaspora contribution to the economy and culture of our country, lobby of foreign and interior interests.